INNOVATIVE ASPECTS OF OPEN INGUINAL HERNIA SURGERY: REDUCING COMPLICATIONS AND PREVENTING RECURRENCES - К. Рахманов; О. Хужамов; С. Давлатов; Б. Хамдамов; С. Янченко; Н. Абдуллаєва; З. Джалілова (Неонатологія, хірургія та перинатальна медицина, 2025)
Inguinal hernias constitute a significant portion of surgical pathology and remain among the most common reasons for seeking surgical consultation. According to the World Health Organization, inguinal hernias occur in 4-5% of the adult population, with men being affected 7 to 10 times more frequently than women.